Cyber deviance among adolescents in Taiwan: Prevalence and correlates. (July 2021) - Chen, Ji-Kang; Chang, Ching-Wen; Wang, Zhiyou; Wang, Li-Chih; Wei, Hsi-Sheng
Highlights: Cyber deviance among adolescents is prevalent in Taiwan. Substance use and school bullying perpetration are associated with the presence of each form of cyber deviance. Male gender, being senior, offline delinquency, and poor life satisfaction are associated with the presence of internet pornography and illegal website visits. Females are more likely to engage in online flaming. School bullying victimization is associated with the presence of internet pornography. Abstract: Using a nationally representative dataset from Taiwan, this paper reports the prevalence of cyber deviance among adolescents and examines its association with gender, age, parental monitoring, substance use, offline delinquent behavior, school bullying and victimization, and life satisfaction. 1, 928 students from junior high (grades 7–9) and senior high (grades 10–12) schools participated in this study. Students were given an anonymous questionnaire including items regarding basic demographics and deviant behaviors in cyber space. The results showed that cyber deviance is prevalent among Taiwanese adolescents. Of all forms, digital/media piracy was the most common, followed by illegal website visits and online flaming, and lastly, by internet pornography. Logistic regression analyses showed that substance use and school bullying perpetration are associated with the presence of all forms of cyber deviance. In addition, females were more likely to engage in online flaming. Male adolescents and seniors and those with offline delinquency history and a low level of life satisfaction were more likely to engage in internet pornography and visiting illegal websites. School bullying victimization was associated with the presence of internet pornography. However, the association between parental monitoring and each form of cyber deviance was non-significant. These findings implied that policy and intervention programs need to tackle cyber deviance at a national level. The potential policy and programs should target senior students and aim to promote adolescent life satisfaction and reduce student's risk of being bullied in school. To maximize their effectiveness, such programs should focus on tackling adolescents' problematic offline behaviors, including substance use, school bullying, and delinquency.